Adenoviral infection in a collection of juvenile inland bearded dragons (Pogona vitticeps). Issue 1 (January 2014) - Doneley, RJT; Buckle, KN; Hulse, L
<x xml:space="preserve">Abstract</x> Case report Juvenile inland bearded dragons (Pogona vitticeps) from a breeding collection in south‐east Queensland were presented at age 6–10 weeks with neurological signs, poor growth and occasional deaths. Histopathological examination revealed that six of eight lizards had multifocal non‐suppurative hepatitis associated with 5–10 μm diameter, smudgy, basophilic, hyaline intranuclear inclusion bodies that marginated the nuclear chromatin. These histological lesions were considered consistent with adenoviral hepatitis. Infection with adenovirus was confirmed positive in one of the eight dragons by PCR for adenoviral DNA. DNA was extracted from formalin‐fixed paraffin‐embedded pooled tissues of the juvenile inland bearded dragons and tested using a nested‐PCR protocol with primers specific for identification of adenovirus. Sequencing of the one PCR‐positive dragon showed 95% nucleotide sequence alignment with agamid atadenovirus 1. Further investigation involved testing the breeding population, including the parents of the affected juveniles. Blood and cloacal samples were collected from the adult population, DNA was extracted and tested by PCR for adenovirus. There was a high percentage of positive results from the samples collected from the breeding population. Conclusion This is the first reported group outbreak of adenoviral disease in bearded dragons in Australia.